'E Pluribus Unum': Identity Politics and the Construction of Ethnicity in Contemporary Ethnic American Prose - Šesnić, Jelena (Array, 2003)
An anaylisis of a work from the US ethnic literary corpus is undertaken to show how contemporary textual representations of ethnicity intersect with and complicate the individual and collective identity construction in contemporary US society especially in view of the strategies of "cultural nationalism", as a project used by various ethnic groups in the 1970s to articulate their distinct identities.